The Effect of Dietary Intervention With High-Oleocanthal and Oleacein Olive Oil in Patients With Early-Stage Chronic Lymphocytic Leukemia: A Pilot Randomized Trial - Rojas Gil, Andrea Paola; Kodonis, Ioannis; Ioannidis, Anastasios; Nomikos, Tzortzis; Dimopoulos, Ioannis; Kosmidis, Georgios; Katsa, Maria Efthymia; Melliou, Eleni; Magiatis, Prokopios (Frontiers in Oncology, 2022)
Oleocanthal and oleacein (OC/OL) have important in vitro and in vivo antitumor properties; however, there is no data about their anticancer activity in humans. The aim of this pilot study was to test if patients at early stage of chronic lymphocytic leukemia (CLL) could adhere to and tolerate an intervention with high OC/OL extra virgin olive oil (EVOO) and if this intervention could lead to any changes in markers related to the disease. Methods: A pilot dietary intervention (DI) was made in patients with CLL in Rai stage 0-II who did not follow any treatment (NCT04215367). In the first intervention (DI1), 20 CLL patients were blind randomly separated into two groups. One group (Α) of 10 patients consumed 40 mL/day of high OC/OL-EVOO (416 mg/Kg OC and 284 mg/Kg OL) for 3 months. A second group (Β) of 10 patients consumed 40 mL/day of low OC/OL (82 mg/Kg OC and 33 mg/Kg OL). After a washout period of 9-12 months, a second intervention (DI2) only with High OC/OL-EVOO for 6 months was performed with 22 randomly selected patients (16 from the DI1 (8 from each group) and 6 new). Hematological, biochemical and apoptotic markers were analyzed in the serum of the patients. In addition, cellular proliferation and apoptosis markers were studied in isolated proteins from Peripheral Blood Mononuclear Cells. Results: The results of the DI1 showed beneficial effects on hematological and apoptotic markers only with High OC/OL-EVOO. During the DI2, a decrease in the white blood cell and lymphocyte count was observed (p=<0.05), comparing 3 months before the intervention and 6 months after it. After 3 and 6 months of DI2, an increase (p=<0.05) was observed in the apoptotic markers ccK18 and Apo1-Fas, as well as in the cell cycle negative regulator p21, and also a decrease in the antiapoptotic protein Survivin, and in the cellular proliferation marker Cyclin D. Conclusions: This is the first clinical trial with High OC/OL-EVOO that indicates that it could be a promising dietary feature for the improvement of CLL inducing the apoptosis of their cancer cells and improving the metabolism of the patients.